OP0303 Mavrilimumab Reduces Pro-Inflammatory Cytokines and CD68 Positive Macrophages in Synovial Explants from Rheumatoid Arthritis Subjects Engrafted Into SCID/Beige Mice. (23rd January 2014) - Bombardieri, M.; Rocher, V.; Mittereder, N.; Carlesso, G.; Herbst, R.; Sleeman, M.; Pitzalis, C.
Abstract : Background: Mavrilimumab, a human antibody to the GMCSFR alpha chain has recently completed a Phase IIa study in subjects with moderate to severe rheumatoid arthritis (Burmester et al., 2012), demonstrating significant clinical outcomes in disease activity. As mavrilimumab does not cross-react with rodent GM-CSFRα we are unable to evaluate it in classical animal models of arthritis therefore we used human RA synovial tissue engrafted onto SCID / Beige mice to provide a better understanding of its mechanism of action Objectives: To evaluate mavrilimumab function in human RA synovial explants in comparison to the anti-TNF therapy, infliximab. Methods: Human RA synovial tissues were isolated from subjects undergoing joint replacement and characterized for inflammatory infiltrate and gene expression as described previously (Humby et al., 2009). Tissue selected for engraftment was characterized by CD68 positive "diffuse" inflammatory infiltrate and broad expression of pro-inflammatory cytokines including GM-CSF expression. Explants were subcutaneously engrafted into male SCID/Beige mice. 14 days after engraftment mice were injected i.p 3 days a week for 2 weeks with either 3 or 0.3 mg/kg mavrilimumab, 3mg/kg infliximab, 3mg/kg isotype control or vehicle alone. At end of study grafts were removed, synovial infiltrate characterized by immunohistochemistry and human pro-inflammatory cytokines quantified by RT-PCR. Results: Mavrilimumab dose dependently reduced CD68 positive macrophages in the synovial explants when compared with synovial explants treated with isotype control antibodies, vehicle alone or infliximab. Due to the relatively low numbers of T and B cells no significant changes in lymphocytes were observed. RT-PCR confirmed significant levels of IL-1, IL-6, TNFα, GMCSF, CCL2, ICAM1 and IFNγ in the isotype and vehicle alone control groups. Mavrilimumab significantly inhibited IL-6, IL-1 and CCL2 in the explant tissue. The level of cytokine suppression was equivalent to that observed with infliximab. Conclusions: Mavrilimumab inhibits human proinflammatory cytokine signals in RA synovial explants that have been engrafted onto SCID/beige mice. In addition mavrilimumab reduces the number of CD68 positive macrophages. These data suggest that mavrilimumab may have direct effects on the function and/or survival of terminally differentiated CD68 positive synovial macrophages. Further analysis is warranted to better understand this mechanism of action. References: Burmester GR et al., (2012) Efficacy and safety of mavrilimumab in subjects with rheumatoid arthritis. Ann Rheum Dis. 2012 Dec 12. [Epub ahead of print]. Humby F et al., (2009). Ectopic lymphoid structures support ongoing production of class-switched autoantibodies in rheumatoid synovium. PLoS Med. 2009 Jan 13;6(1): Disclosure of Interest: M. Bombardieri Grant/research support from: MedImmune Ltd, V. Rocher: None Declared, N. Mittereder Employee of: MedImmune LLC, G. Carlesso Shareholder of: Astrazeneca, Employee of: MedImmune LLC, R. Herbst Shareholder of: Astrazeneca, Employee of: MedImmune LLC, M. Sleeman Shareholder of: Astrazeneca, Employee of: MedImmune Ltd, C. Pitzalis Grant/research support from: MedImmune Ltd, Consultant for: MedImmune Ltd